Severe Stroke Patients With Left-Sided Occlusion of the Proximal Anterior Circulation Benefit More From Thrombectomy - Li, Zibao; Chu, Zhaohu; Zhao, Shoucai; Ma, Lingsong; Yang, Qian; Huang, Xianjun; Zhou, Zhiming (Frontiers in Neurology, 2019)
Background and Purpose: Endovascular thrombectomy improves the functional independence of patients with proximal anterior circulation occlusion. However, a subset of patients fail to benefit from thrombectomy procedures, the reasons for which remain poorly defined. In this study, we investigated whether the effectiveness of thrombectomy was affected by left- or right-sided occlusion among patients with similar stroke severities. Methods: Patients with proximal anterior circulation occlusion (internal carotid or M1 of middle cerebral artery) treated with the Solitaire stent retriever within 8 hours of the onset of acute ischemic stroke were enrolled from the Yijishan Hospital of Wannan Medical College. Stroke severity was measured using the National Institutes of Health Stroke Scale (NIHSS) on admission. The functional outcomes were assessed using the modified Rankin scale (mRS) at 90 days. Results: We enrolled 174 patients including 90 left-sided occlusion and 84 right-sided occlusion. The NIHSS scores on admission were higher in the left-sided (median, 19; interquartile range, 16 to 20) compared to the right-sided occlusion group (median, 15, interquartile range, 13 to 18) (P < 0.001). Following adjustment for potential risk factors, patients with left-sided occlusion had higher rates of functional independence (mRS ≤ 2) and lower rates of mortality (mRS = 6) compared to the right-sided occlusion patients (39.5% vs. 19.6% and 28.9% vs. 47.8%, respectively) in the severe stroke group (NIHSS ≥ 15). Conclusions: In severe stroke patients with proximal anterior circulation occlusion, stent retriever thrombectomy within 8 hours of the onset of symptoms provides more benefits to left-sided occlusion.